Anti-TNFα therapy for chronic inflammatory disease in kidney transplant recipients: Clinical outcomes. Issue 41 (October 2016) - Garrouste, Cyril; Anglicheau, Dany; Kamar, Nassim; Bachelier, Claire; Rivalan, Joseph; Pereira, Bruno; Caillard, Sophie; Aniort, Julien; Gatault, Philippe; Soubrier, Martin; Sayegh, Johnny; Colosio, Charlotte; et al.
Abstract : Abstract: Anti-tumor necrosis factor-α (TNFα) therapy has improved the prognosis of many chronic inflammatory diseases. It appears to be well-tolerated by liver-transplant patients. However, their use and their safety in kidney-transplant patients have yet to be determined. In this retrospective study, we identified 16 adult kidney-transplant patients aged 46.5 years (34–51.8) who received anti-TNFα therapy from 7 kidney transplantation centers. The indications for this treatment included: chronic inflammatory bowel disease (n = 8), inflammatory arthritis (n = 5), AA amyloidosis (n = 1), psoriasis (n = 1), and microscopic polyangiitis (n = 1). Anti-TNFα therapies resulted in a clinical response in 13/16 patients (81%). Estimated glomerular filtration rates (MDRD-4) were similar on day 0 and at 24 months (M24) after anti-TNFα treatment had been initiated (41 [12–55] and 40 [21–53] mL/min/1.73 m 2, respectively). Two allograft losses were observed. The 1st case was due to antibody-mediated rejection (M18), while the 2nd was the result of AA amyloidosis recurrence (M20). There were several complications: 8 patients (50%) developed 23 serious infections (18 bacterial, 4 viral, and 1 fungal) and 4 developed cancer. Five patients died (infection n = 2, cardiac AA amyloidosis n = 1, intraalveolar hemorrhage following microscopic polyangiitis n = 1, and acute respiratory distress syndrome n = 1). On univariate analysis, recipient age associated with death ( P = 0.009) and infection development ( P = 0.06). Using anti-TNFα therapies, remission can be achieved in chronic inflammatory diseases in kidney-transplant patients. However, concommitant anti-TNFα and immunosuppresive therapies must be used with caution due to the high risk of infection, particularly after the age of 50.